The Role of Tahfidz Teachers in Improving Students Discipline in Memorizing the Quran - Fisa Bela Masithoh; Meti Fatimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyse the role of tahfidz teachers in improving Quran memorisation discipline among students at MTs Negeri 5 Demak, Central Java. This research focuses on the implementation of the tahfidz program within a formal madrasah context by involving tahfidz teachers and students participating in the program. The study emphasises that tahfidz teachers play a multifaceted role, serving as teachers, motivators, guides, evaluators, and facilitators, while adapting learning methods to suit student characteristics. Structured learning strategies, including routine schedules, varied methods, periodic evaluation and monitoring, as well as providing intrinsic and extrinsic motivation, are key supporting factors in building student consistency and commitment. Madrasah environmental support and parental involvement also strengthen student discipline in Quran memorisation. The results show that the interaction between the teachers role, learning strategies, student motivation, and environmental support creates sustainable and high-quality memorisation discipline. This study is limited to a single madrasah setting, namely MTs Negeri 5 Demak, so the findings may not be generalised to other regions or educational institutions with different characteristics. These findings provide a theoretical and practical basis for developing tahfidz programs in formal madrasahof the document are as follows. The Abstract should be 150 – 250 words and written in English. This article is also available at gb777